THE INFLUENCE OF COMPANY SIZE, ASSET GROWTH, AND SALES GROWTH ON CAPITAL STRUCTURE IN THE AUTOMOTIVE SUB-SECTOR AND AUTOMOTIVE COMPONENTS IN THE INDONESIA STOCK EXCHANGE FOR THE 2016-2021 PERIOD - Zulkarnain, Iskandar (PENANOMICS: International Journal of Economics, 2023)
This study aims to determine and analyze the effect of company size, asset growth, and sales growth on capital structure in the automotive and automotive components sub-sector on the Indonesia Stock Exchange for the 2016-2021 period. This study uses secondary data with associative quantitative research methods. The total population used in this study were 7 companies. The sampling technique in this study uses the techniquepurposive sampling which determines the criteria to be applied to a sample of 11 companies. The results showed that company size has a positive but not significant effect on capital structure, asset growth has a positive and significant effect on capital structure, and sales growth has a negative but not significant effect on capital structure.